2011
DOI: 10.1097/opx.0b013e31820846ac
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of a Customized Free-Form Progressive Add Lens Spectacle

Abstract: There were statistically significant preferences for the optically customized free-form lenses over the non-free-form lenses. Subjects also reported a wider field of undistorted vision when looking through the reading zone of the test spectacles. Although standard clinical vision assessments are not sufficiently refined to detect important objective differences between the spectacle types, customization taking into account back vertex distance, segment height, pantoscopic tilt, and wrap angle can result in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 8 publications
(9 reference statements)
1
42
0
1
Order By: Relevance
“…To ensure our subjects were properly fit with the PALs prescription, an Optometrist and Optician each with over 20 years of experience ensured that the PALs were properly fitted to the subjects. Other studies report that prescription, frame size, fitting parameters and free-form manufacturing to design patient specific PALs do impact objective visual performance 90 . While our results do not show that the interpupillary distance was correlated to PALs acceptance, future studies may wish to provide a more detailed studied that concentrates on a larger distribution of interpupillary distances.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure our subjects were properly fit with the PALs prescription, an Optometrist and Optician each with over 20 years of experience ensured that the PALs were properly fitted to the subjects. Other studies report that prescription, frame size, fitting parameters and free-form manufacturing to design patient specific PALs do impact objective visual performance 90 . While our results do not show that the interpupillary distance was correlated to PALs acceptance, future studies may wish to provide a more detailed studied that concentrates on a larger distribution of interpupillary distances.…”
Section: Discussionmentioning
confidence: 99%
“…During driving, by viewing an object at a distance paired with vision disturbance; peripheral blur, unwanted astigmatism and distortion. Han et al (2011) reported that progressive additional lens (PALs) wearer was more satisfied as compared to the use bifocal lens. However, most of them were uncomfortable with distortion at the peripheral vision.…”
Section: Correlation Of Quality Of Vision Symptoms With Total Satisfmentioning
confidence: 99%
“…This may occur due to the easier adaptation of the early presbyope as compared to the late presbyope. A previous study by Han et al, 2011, has compared patients" satisfaction with progressive lenses with other types of presbyopic correction. They revealed pout that most the subjects involved has were satisfied with progressive lenses rather than other type of lenses (Han et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos já apontam a superioridade dessas lentes em ensaios clínicos. 9,10 Cuidado especial deve ser considerado na conferência dessas lentes em lensômetros comuns. Ao descer o garfo de sustentação para medir, principalmente, o poder de perto, encontrar-se-ia valores dióptricos diferentes dos prescritos (Figura 2-A).…”
unclassified